Yield of the Mutant (M6) Short Stem of Mentik Wangi Rice Varieties Resulting from Gamma Ray Irradiation 300 Gray - Yunus, Ahmad; Mulyawati, Rizky; Parjanto, Parjanto (Journal of Biodiversity and Biotechnology, 2021)
Mentik Wangi is one of Indonesia's most popular rice germplasm sources due to its delicate, fluffy texture and arom aroma. Farmers switch to better varieties with high yields due to field challenges in cultivating fragrant rice. The plants are quite tall, harvest time is long, and yield is low; therefore farmers switch to superior varieties with high yields. The purpose of this research was to obtain information on how much yield of 14 mutant rice lines produce and to find mutant lines with short stems and high yields that could be developed to new varieties. The research was conducted at the Tegalgondo Rice Seed Garden Agricultural Land between June to October 2020. This study used a Completely Randomized Block Design (CRBD) with a single factor. Each treatment was repeated three times. The data obtained analyzed with analysis of variance and followed with Duncan Multiple Range Test at 5% level if any significant influences were obtained. The results of this research showed that 14 Mentik Wangi rice lines yields were ranging from 6.70 to  8.21 tons ha-1.Stems from 9 lines with high yields were M6-MW3-G10-14-2, M6-MW3- G12-1-17,  M6-MW3-G5-21-3,  M6-MW3-G5-21-14,  M6-MW3-G6-17-14-4,  M5-MW3-G6-20-9-16,  M6-MW3-G1-1-2  M5-MW3-G1-5-47,  M6-MW3-G6-10-9-26.  These lines were potential candidates for new high-yielding varieties, which would then considered to be evaluated for higher yields or multilocation tests before becoming an official new varieties.Keywords: mentik wangi; mutations; short stem; yield potential;